Analysis Of Profile and Competence of U19 Football Coaches in Pemalang Regency - Adnan, Naufal; Nilawati, Ika; Herdinata, Guntur Ratih Prestifa; Aristiyanto, Aristiyanto; Setiawan, Fredy Eko; Wicaksono, Maulana Tegar; Amin, Nur; Nasri, Nasri (AIBPM Publisher, 2025)
Football in Indonesia continues to grow rapidly, as reflected in the increasing number of clubs across various regions, including Pemalang Regency. However, the presence of many clubs has not translated into improved achievements due to the absence of a structured development system. Key issues include limited communication with stakeholders, unstructured training programs, and the lack of qualified coaches capable of designing and evaluating effective training. This study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The subjects consisted of 48 respondents: 16 administrators, 16 coaches, and 16 players. Data validity was ensured using source triangulation, while analysis was conducted through data reduction and presentation. The findings indicate that coaches generally demonstrate good attitudes during training and matches, but most lack coaching licenses and the ability to design structured programs. Of 16 U19 clubs, only 3 coaches held official licenses and 1 had a youth assistant license. Overall, the results highlight that although coaches show positive behavior, the absence of licensing and structured training knowledge hinders the development of U19 football in Pemalang Regency.